Penyuluhan Kepedulian Lingkungan melalui Video Edukatif dan Permainan pada Siswa SD Negeri 23 Lubuk Lagak - Ifa Auliandini; Risma Wati; Anrian Irpansah; Risa Nirpana; Mulpi Iman Saputra; Beryaldi Agam; Indra Mahyudi S; Nurul Fatimah Yunita; Noferianto Sitompul (Pakis Journal Institute, 2026)
The education activity titled “Let’s Protect Fish Habitats, Beautiful Rivers Without Waste” was conducted at SD Negeri 23 Lubuk Lagak with the aim of improving students’ knowledge and awareness of environmental cleanliness, particularly rivers as fish habitats. The methods used included educational video screenings, interactive material delivery, and educational games to enhance student engagement. The evaluation was carried out through pre-test and post-test assessments. The results showed a significant improvement, with the average score increasing from 70.71 in the pre-test to 89.28 in the post-test. Observations also indicated that students were highly enthusiastic and actively participated throughout the activity, demonstrating improved understanding of fish types, the impacts of pollution, and the importance of maintaining river cleanliness. Support from the school also contributed to the success of the program. Therefore, it can be concluded that the use of educational videos and games is an effective strategy in enhancing environmental awareness and understanding among elementary school students.